2001
DOI: 10.1191/026921601675617254
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of the lived experience of hope in patients with cancer in palliative home care

Abstract: The aim of this study was to illuminate the meaning of the lived experience of hope in patients with cancer in palliative home care. Narrative interviews with 11 patients were interpreted using a phenomenological-hermeneutic method, inspired by Ricoeur. The findings revealed a tension between hoping for something, that is a hope of getting cured, and living in hope, that is reconciliation and comfort with life and death. This tension is highlighted, according to the views of the French philosopher Gabriel Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
232
0
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(268 citation statements)
references
References 18 publications
18
232
0
18
Order By: Relevance
“…28,[33][34] To our knowledge, fewer studies have been conducted with regard to the views of PC patients and their families on hope. Benzein et al 15 interviewed 11 PC patients with cancer about their views on hope; the types of hope identified in their study included "a hope of being cured," "a hope of living as normally as possible," "a presence of confirmative relationships," and "reconciliation with life and death. " In a study with four PC patients as subjects, Flemming 35 reported the following types of hope: the hope of controlling disease progression, the existence and presence of family members and an anticipated future with them, and medical or nursing staff taking an interest in them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,[33][34] To our knowledge, fewer studies have been conducted with regard to the views of PC patients and their families on hope. Benzein et al 15 interviewed 11 PC patients with cancer about their views on hope; the types of hope identified in their study included "a hope of being cured," "a hope of living as normally as possible," "a presence of confirmative relationships," and "reconciliation with life and death. " In a study with four PC patients as subjects, Flemming 35 reported the following types of hope: the hope of controlling disease progression, the existence and presence of family members and an anticipated future with them, and medical or nursing staff taking an interest in them.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, in the context of a terminal illness, hope for a cure is often lost. Authors have described hope in the setting of a terminal illness as a multidimensional 12 and a dynamic process 6,15 that for most patients requires coming to terms with multiple losses in a changing reality. 6 Therefore, how can clinicians discuss the future with terminally ill cancer patients and yet still help patients to cope and foster hope?…”
mentioning
confidence: 99%
“…In addition, because previous reports suggested that finding a sense of meaning or transcendence ameliorates the experience of suffering, 41,44 maintaining and/or fostering hope, which may enhance these elements, may be another amelioration strategy. [45][46][47] In view of these findings, comprehensive care, including physical, psychosocial, and spiritual dimensions of patients as whole persons, namely, excellent palliative care, is indispensable for these patients. 48 One study suggested that continuing comprehensive care provided by palliative care teams can reduce the risk of suicide even among terminally ill cancer patients.…”
Section: Suicidal Ideation As Sufferingmentioning
confidence: 99%
“…Attempts to inspire sometimes evolve into demands, thus cognitively tend to draw the patient from the present moment into thinking about an insecure future (Sandén, 2006). This is adjacent to Benzein’s conclusions about hope in palliative care, which distinguishes “living with hope” from “to hope for something”: “living with hope”, that is, being hopeful relating to what is present; “to hope for something”, that is, hoping relating to future and changes (Benzein, Norberg, & Saveman, 2001). Most of our respondents had a fairly good prognosis.…”
Section: Resultsmentioning
confidence: 96%